Adjustment Factors to Account for the Effect of Bridge Deck Horizontal Curvature on the Seismic Response of Concrete Box-Girder Bridges in California. Issue 2 (May 2018) - Mangalathu, Sujith; Jeon, Jong-Su
This research suggests adjustment factors to account for the effect of bridge deck horizontal curvature on the probabilistic seismic demand model (PSDMs) and fragility curves of concrete box-girder bridges in California. For this purpose, typical configurations of horizontally curved bridges in California are selected to create detailed three-dimensional (3-D) probabilistic bridge models with different levels of bridge deck horizontal curvature. Simulation results from the nonlinear time history analysis (NLTHA) of bridges are used to compare the PSDM of individual bridge components using a statistical technique called analysis of covariance (ANCOVA). Comparison results are used to group bridge classes and to suggest adjustment factors. Grouping results indicate that the PSDMs of unseating and bearing displacement are statistically significant for bridges with different levels of deck horizontal curvature. The effect of deck curvature and the use of the modification factors are demonstrated in this paper through the generation of fragility curves.